Mental Health and Cardiovascular Disease: Challenges for Counsellors - Berry, Tanya; Walsh, John (Canadian Journal of Counselling and Psychotherapy, 2007)
Tremendous gains have been made in treating the effects of cardiovascular disease (CVD). Across the last few decades, the survival rates following a vascular accident, that is, a stroke or heart attack, have increased steadily and substantially. Unfortunately, this success has resulted in a corresponding increase in the number of individuals with reduced physical or psychological functioning due to cardiac related disability. In this paper, we discuss the psychological challenges that confront individuals recovering from such events. In the closing section, we describe the crucial role that counsellors might play in aiding the rehabilitation of cardiac clients.